Against security: how we go wrong at airports, subways, and other sites of ambiguous danger - Molotch, Harvey (Princeton, NJ., 2012)
"Remember when an unattended package was just that, an unattended package? Remember when the airport was a place that evoked magical possibilities, not the anxiety of a full-body scan? In the post-9/11 world, we have become focused on heightened security measures, but do you feel safer? Are you safer? Against Security explains how our anxieties about public safety have translated into command-and-control procedures that annoy, intimidate, and are often counterproductive. Taking readers through varied ambiguously dangerous sites, the prominent urbanist and leading sociologist of the everyday, Harvey Molotch, argues that we can use our existing social relationships to make life safer and more humane. He begins by addressing the misguided strategy of eliminating public restrooms, which deprives us all of a basic resource and denies human dignity to those with no place else to go. Subway security instills fear through programs like "See Something, Say Something" and intrusive searches that have yielded nothing of value. At the airport, the security gate causes crowding and confusion, exhausting the valuable focus of TSA staff. Finally, Molotch shows how defensive sentiments have translated into the vacuous Freedom Tower at the World Trade Center site and massive error in New Orleans, both before and after Hurricane Katrina. Throughout, Molotch offers thoughtful ways of maintaining security that are not only strategic but improve the quality of life for everyone. "